Inventarisasi Tumbuhan Obat untuk Kesehatan Reproduksi dalam Mamar Desa Beaneno, Kecamatan Sasitamean, Kabupaten Malaka - Mayang Gracelia Bessie; Wilhelmina Seran; Norman P. L. B. Riwu Kaho; Astin E. Mau (Wana Lestari, 2026)
East Nusa Tenggara Province has a diversity of medicinal plants and traditional culture in using them. The use of plants as medicine has also been used for a long time by the people of Beaneno Village, which is one of the villages administratively located in Sasitamean District, Malaka Regency, NTT Province. The Beaneno Village community uses land using the Mamar Agroforestry system which has been managed for generations. This research aims to inventory plant types, the properties of these plants and how to process plants as medicine for reproductive health by the people of Beaneno Village. Data collection techniques use the snowball interview method, observation, vegetation analysis with the exploration method to obtain plant locations and the quadrant method to analyze vegetation and literature studies. Data analysis uses quantitative analysis to determine the importance of species, diversity value, evenness value and species richness value. In the results of the observations, it was found that there were 8 types of plants with medicinal properties, with the composition of the vegetation showing that the types of plants with the highest herbaceous habit were 3 types, 2 types of trees, 2 types of shrubs and 1 type of liana. Types of medicinal plants that have important value. The largest type is Desmodium triflorum (76.04) for seedling level. The diversity index value for medicinal plants in Beaneno Village mammar is 1.778 (medium), the evenness index value is 0.7394 (fairly even) and the seedling category, the value is 1.325 (low).